2017
DOI: 10.3813/aaa.919061
|View full text |Cite
|
Sign up to set email alerts
|

Generating Sequences of Acoustic Scintillations

Abstract: Spatial and temporal inhomogeneities in temperature and wind velocity affect sound propagation resulting in amplitude and phase fluctuations called scintillations. Acomputationally efficient method is presented to generate sequences of scintillations. The method, already used in the field of wireless communication to predict the performance of wireless communication links, could be used in the field of acoustics to create more perceptually valid auralizations. AG aussian spectrum and as pherical wavefront is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Further research is needed to fully quantify the change in measured noise intensity caused by wind-gusts and develop a methodology to introduce them with the required intensity into the synthesis process. Some work in this regard is being carried out by other organizations such as in [25]. It would also be beneficial for future comparisons to limit the effect of wind-gusts by either choosing a calmer day (average wind speeds on the day of the measurement were around 3 m/s), adding wind-screens around the microphone or reducing the height of the microphone from its current position at 10 m altitude.…”
Section: 2mentioning
confidence: 99%
“…Further research is needed to fully quantify the change in measured noise intensity caused by wind-gusts and develop a methodology to introduce them with the required intensity into the synthesis process. Some work in this regard is being carried out by other organizations such as in [25]. It would also be beneficial for future comparisons to limit the effect of wind-gusts by either choosing a calmer day (average wind speeds on the day of the measurement were around 3 m/s), adding wind-screens around the microphone or reducing the height of the microphone from its current position at 10 m altitude.…”
Section: 2mentioning
confidence: 99%
“…Hence, turbulence does not affect the resulting sound paths. It can be included during the auralization process using time-variant filters [15]. Furthermore, a common simplification for the atmosphere is the so-called stratified medium [7].…”
Section: Stratified Atmosphere Modelmentioning
confidence: 99%
“…The overall attenuation is acquired by integrating this parameter along the ray path using left Riemann sums. Another frequency-dependent effect to be considered is amplitude and phase fluctuations caused by turbulent scattering [15,27].…”
Section: Auralization Parametersmentioning
confidence: 99%
“…It was further found that the inclusion of the ground effect and amplitude fluctuations due to atmospheric turbulence 22 both serve to increase realism and plausibility of auralized flyovers. Ground effect, defined as the spectral pattern induced by interference of direct and ground reflected sound, is simulated here by an additional signal path that interferes with the direct sound signal.…”
Section: Ve Propagation Effectsmentioning
confidence: 99%